Correlation between magnetic properties of electrodeposited Co(P) and NH4Cl concentrations in the electrolyte - Lee, KH; Kim, GH; Jeung, WY (ELSEVIER SCIENCE INC, 2002)
The effect of ammonium chloride on the electrodeposition process and resulting magnetic properties of Co(P) alloy films was investigated. It was observed that the magnetic properties of the films varied extensively with the ammonium chloride contents in the solution. Cyclic voltammetry was employed as an electroanalytical technique to characterize the variation of interfacial polarization at different electrolyte compositions. In addition, microstructural characterization of electrodeposited Co(P) thin films by transmission electron microscopy revealed a significant increase in both grain size and preferred orientation of Co(P) grains with ammonium chloride contents. Results of characterizations indicated that the addition of ammonium chloride controlled the kinetics of electrocrystallization of Co(P) by modifying the charge transfer process and thus gave rise to increased grain size and preferred orientation in the Co(P) thin films. These microstructural features provide reasonable explanation on the variation of the magnetic properties of electrodeposited Co(P) films with the amount of ammonium chloride in the solution. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: ALLOYS